World of KidsMath: Adventure game-based learning Mathematics for preschool children / Muhammad Amirul Hakim Amri - Amri, Muhammad Amirul Hakim (Faculty of Computer and Mathematical Sciences, 2015)
World of KidsMath is an adventure game which will act as a tool to learn about mathematics concept and operations in mathematics. World of KidsMath consists of two part; game and learning part which will be processed separately. Game part as a way to attract children attention while learning part is a tool for teaching mathematics in term of increasing children mathematical problem solving. This project shows on how the learning and game module developed based on mathematics concept. Based on the concept, which only use addition and subtraction operation, the project only suitable for preschool children age 6 years old in Sekolah Tadika Jaim Merlimau. Preschools children’s participation and involvement in this project, will cause a learning process to happen. This will leads to the development of preschool children’s critical thinking, development, and problem solving skills. The framework of this project includes questionnaire, pre-test, post-test and survey. The results on the framework were conducted and all the positive feedback were used in developing this project.